Post-Adoption Variations in Usage and Value of E-Business by Organizations: Cross-Country Evidence from the Retail Industry - Zhu, Kevin; Kraemer, Kenneth L (Information systems research, 2005)
Grounded in the innovation diffusion literature and the resource-based theory, this paper develops an integrative research model for assessing the diffusion and consequence of e-business at the firm level. Unlike the typical focus on adoption as found in the literature, we focus on postadoption stages, that is, actual usage and value creation. The model thus moves beyond dichotomous "adoption versus nonadoption" and accounts for the "missing link"actual usageas a critical stage of value creation. The model links technological, organizational, and environmental factors to e-business use and value, based on which a series of hypotheses are developed. The theoretical model is tested by using structural equation modeling on a dataset of 624 firms across 10 countries in the retail industry. To probe deeper into whether e-business use and value are influenced by economic environments, two subsamples from developed and developing countries are compared. The study finds that technology competence, firm size, financial commitment, competitive pressure, and regulatory support are important antecedents of e-business use. In addition, the study finds that, while both front-end and back-end capabilities contribute to e-business value, back-end integration has a much stronger impact. While front-end functionalities are becoming commodities, e-businesses are more differentiated by back-end integration. This is consistent with the resource-based theory because back-end integration possesses the value-creating characteristics of resources (e.g., firm specific, difficult to imitate), which are strengthened by the Internet-enabled connectivity. Our study also adds an international dimension to the innovation diffusion literature, showing that careful attention must be paid to the economic and regulatory factors that may affect technology diffusion across different countries.